APOE genotype determines cell-type-specific pathological landscape of Alzheimer’s disease - Li, Zonghua; Martens, Yuka A.; Ren, Yingxue; Jin, Yunjung; Sekiya, Hiroaki; Doss, Sydney V.; Kouri, Naomi; Castanedes-Casey, Monica; Christensen, Trace A.; Miller Nevalainen, Lindsay B.; Takegami, Nanaka; Chen, Kai; et al. (Neuron (Cambridge, Mass.), 2025)
The apolipoprotein E (APOE) gene is the strongest genetic risk modifier for Alzheimer’s disease (AD), with the APOE4 allele increasing risk and APOE2 decreasing it compared with the common APOE3 allele. Using single-nucleus RNA sequencing of the temporal cortex from APOE2 carriers, APOE3 homozygotes, and APOE4 carriers, we found that AD-associated transcriptomic changes were highly APOE genotype dependent. Comparing AD with controls, APOE2 carriers showed upregulated synaptic and myelination-related pathways, preserving synapses and myelination at the protein level. Conversely, these pathways were downregulated in APOE3 homozygotes, resulting in reduced synaptic and myelination proteins. In APOE4 carriers, excitatory neurons displayed reduced synaptic pathways similar to APOE3, but oligodendrocytes showed upregulated myelination pathways like APOE2. However, their synaptic and myelination protein levels remained unchanged or increased. APOE4 carriers also showed increased pro-inflammatory signatures in microglia but reduced responses to amyloid-β pathology. These findings reveal APOE genotype-specific molecular alterations in AD across cell types. [Display omitted] •Transcriptomic changes in human brains vary with APOE genotype in AD•APOE2 carriers preserve synaptic proteins and MBP in AD•APOE4 carriers show myelin loss without AD and higher dMBP than APOE3 in AD•APOE4 microglia show inflammatory gene upregulation in AD but reduced Aβ response Using single-nucleus RNA sequencing on post-mortem brains from control subjects and Alzheimer’s disease patients, Li et al. revealed APOE-genotype-specific molecular alterations across distinct brain cell types associated with AD. This study offers a valuable resource for further elucidating the role of APOE in AD pathogenesis.